2007
DOI: 10.2337/dc06-2220
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated Fat–Rich Diet Prevents Central Body Fat Distribution and Decreases Postprandial Adiponectin Expression Induced by a Carbohydrate-Rich Diet in Insulin-Resistant Subjects

Abstract: OBJECTIVE -Central obesity is associated with insulin resistance through factors that are not fully understood. We studied the effects of three different isocaloric diets on body fat distribution, insulin sensitivity, and peripheral adiponectin gene expression. RESEARCH DESIGN AND METHODS-Eleven volunteers, offspring of obese type 2 diabetic patients with abdominal fat deposition, were studied. These subjects were considered insulin resistant as indicated by Matsuda index values Ͻ4 after an oral glucose tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
142
1
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(173 citation statements)
references
References 41 publications
9
142
1
9
Order By: Relevance
“…Several previous studies have shown a decrease in leptin in response to mixed and high-fat meals in healthy individuals [12], but not in subjects with T2D [37]. Our results contrast to a longer-term study where lower plasma leptin responses to a test meal were observed in 11 REL after 3 weeks on a MUFA-rich diet versus a SFArich diet [38]. While others found decreased baseline and insulin-stimulated LEP expression in the main site of leptin synthesis (adipose tissue) in male REL [23], we only found differences in muscle.…”
Section: Discussioncontrasting
confidence: 99%
“…Several previous studies have shown a decrease in leptin in response to mixed and high-fat meals in healthy individuals [12], but not in subjects with T2D [37]. Our results contrast to a longer-term study where lower plasma leptin responses to a test meal were observed in 11 REL after 3 weeks on a MUFA-rich diet versus a SFArich diet [38]. While others found decreased baseline and insulin-stimulated LEP expression in the main site of leptin synthesis (adipose tissue) in male REL [23], we only found differences in muscle.…”
Section: Discussioncontrasting
confidence: 99%
“…Animal model research suggests that dietary PUFA may protect against obesity through mechanisms linked to fat deposition and hormonal regulatory systems (Wang et al, 2002). Human studies show that energy deficits alone do not change body fat distribution (Redman et al, 2007), but this is not the case with fat modification (Summers et al, 2002;Panigiagua et al, 2007). Dietary fat can influence the expression of genes associated with body weight regulatory systems (Summers et al, 2002;Wang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after following a MUFA enriched-diet with a mix of olive oil and nuts for 4-weeks, a significant reduction in body weight and fatness was observed in overweight and obese man (38). Furthermore, although an olive oilenriched diet did not change body weight and fatness of the obese individuals, it prevented central body fat distribution leading to an improvement in insulin sensitivity (39). When two MUFA-enriched diets within a 6-months weight reduction program were compared (olive oil versus rapeseed), no significant difference between then was verified, yet, both were effective in reducing body weight, fat mass, and waist circumference with an increment in lean mass (40).…”
Section: Obesitymentioning
confidence: 93%